PELATIHAN PENGGUNAAN FASILITAS PRAKTIK JURUSAN TEKNIK KENDARAAN RINGAN DI SMK NEGERI SAPTOSARI GUNUNGKIDUL DAERAH ISTIMEWA YOGYAKARTA - Gunadi, Gunadi; Sofyan, Herminarto; Yudianto, Aan (Jurnal Pendidikan Vokasi Otomotif, 2023)
The demands of technological developments require educational institutions to update and equip practical facilities to support the achievement of graduate targets. This requires resources capable of operating and using these practice facilities. This Community Service Program aims to provide training on the use of student practice facilities in the form of Smoke Testers and Gas Analyzers to teachers and technicians of the Automotive Light Vehicle Engineering Department at SMK N Saptosari, Gunungkidul Regency, Special Region of Yogyakarta. With this training, it is hoped that teachers and employees will be able to use the equipment in accordance with procedures. The target audience for this activity are teachers and employees in the Automotive Light Vehicle Engineering Department at SMK N Saptosari. The method used in this activity is through exposure delivered by experts which is then followed by hands-on practical training activities in the use of Smoke Tester and Gas Analyzer tools. The indicator for achieving the objectives in this PPM activity is increasing the knowledge and understanding of the target audience about the use of practical facilities in the form of Smoke Tester and Gas Analyzer tools. The results of the evaluation conducted using a questionnaire showed that the training participants were very satisfied with the activities carried out and wished that these activities be carried out continuously.